2008
DOI: 10.1210/jc.2006-2656
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Thyrotropin-Releasing Hormone Stimulation Test in Diagnosis of Congenital Central Hypothyroidism in Infants

Abstract: lp;&-8qContext:A shortage of thyroid hormone during prenatal life and the first years after birth results in a spectrum of neuropsychological disorders, depending on the duration and severity of the deficiency. In the case of congenital hypothyroidism of central origin (CH-C), the majority of patients have multiple pituitary hormone deficiencies (MPHD). This condition poses an additional threat to postnatal central nervous system development, primarily on account of neuroglycopenia due to ACTH/cortisol deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 40 publications
4
26
0
1
Order By: Relevance
“…In the present study and in line with a previous report [27], CPHD appears to be more frequent in boys, even though in most patients, genital anomalies were undetected by pediatricians before their referral to us. Thus, the different prevalence between genders is apparently not related to the presence of genital anomalies.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study and in line with a previous report [27], CPHD appears to be more frequent in boys, even though in most patients, genital anomalies were undetected by pediatricians before their referral to us. Thus, the different prevalence between genders is apparently not related to the presence of genital anomalies.…”
Section: Discussionsupporting
confidence: 92%
“…8 These studies have also shown that low baseline TSH, as seen in our case, are more likely with pituitary cause for TSH deficiency. In this background and as TRH is not readily available for clinical use in India, we considered isolated TSH deficiency and proceeded with mutation analysis of TSHB gene.…”
Section: Discussionsupporting
confidence: 71%
“…In the neonates, CeH can be identifi ed only by screening programs based on concomitant TSH and total T4 measurements in the dry blood spot [ 4 -8 ]. CeH confi rmation by serum FT4 and abnormal TSH response to TRH testing may reveal the risk of CPHDs and impending adrenal crisis [ 8 ]. CPHDs represent the more frequent forms of neonatal CeH.…”
Section: Inheritable Ceh Formsmentioning
confidence: 99%